FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI IKAN DI KABUPATEN KAMPAR - Trian Zulhadi; Budi Azwar (Fakultas Perikanan dan Kelautan, Universitas Riau, 2011)
This study aims to determine the factors that affect fish production(Y) in Kampar regency, the factors that influence the labor factor(X1) and capital factors (X2). The data used are time series data are annualdata from the years 2002 -2008, the source of data is secondary data offish production data, employment data, and data capital, production data takendirectly from the central bureau of statistics (BPS) Kampar district. Analysisof the data used in this study is to use multiple linear regressionmethod to determine the factors affecting fish production in Kampar regency.From the research found a significant relationship exists between labor(X1), capital (X2) tonumber offish production (Y) inKampar regency.For the labor factor of 1.513 X1 andthe capital factor of 0.023 X2 is meaningful for every 1 percent increase in labor force, the number of fish production increasedby 151.3 tonnes of fish, and every 1 percent increase in the amount of capitalincrease fish production increased by 2, 3 tonnes offish production in theKampar district. To prove whether or not a significant factor labor (X1) andcapital (X2) is done using t test, based on the results significantly with the levelof 5%. So is the test f siginikan at level 5%.